2013
DOI: 10.1186/1752-4458-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment needs, diagnoses and use of services for acutely admitted psychiatric patients in northwest Russia and northern Norway

Abstract: BackgroundWe compared demography, diagnoses and clinical needs in acutely admitted psychiatric hospital patients in northwest Russia and northern Norway.MethodAll acutely admitted psychiatric patients in 1 psychiatric hospital in north-west Russia and 2 in northern Norway were in a three months period assessed with HoNOS and a Norwegian form developed to study acute psychiatric services (MAP). Data from a total of 841 patients were analysed (377 Norwegian, 464 Russian) with univariate and multivariate statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Another study found that women who had always been admitted voluntarily had a higher standardized mortality rate [ 70 ]. A study comparing characteristics of patients in one Russian and two Norwegian hospitals found that a higher proportion of patients in the Russian hospital were voluntary [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that women who had always been admitted voluntarily had a higher standardized mortality rate [ 70 ]. A study comparing characteristics of patients in one Russian and two Norwegian hospitals found that a higher proportion of patients in the Russian hospital were voluntary [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants were included from three hospitals: Archangelsk Clinical Psychiatric Hospital, Russia (seven acute wards with 900 emergency psychiatric beds), Nordland County Psychiatric Hospital, Norway (two acute wards with 100 emergency psychiatric beds), and University Hospital of North Norway (three acute wards with 147 emergency psychiatric beds). Further details regarding the study contexts have been published elsewhere [ 26 ]. All admissions to these wards were included for three months in 2005 in Norway, and between 2008 and 2009 in Russia.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected during clinical consultations by the patients’ therapists (psychiatrists or psychologists). Therapists responsible for the assessments were systematically trained and details of the training procedure are published elsewhere [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking treatment privately is also an option for those who can afford it. Assessment and treatment within primary care is rare [15,16,18,19]. However if those with depression and anxiety are more likely to attend general health care services this may equate with missed opportunities for care.…”
Section: Introductionmentioning
confidence: 99%